On the excessive nature of the tax authority interim measures - A. V. Ilin (Вестник университета, 2024)
The study subject is the interim measures’ institute of the tax authority.   The study relevance is due to the incomplete decisions’ execution of tax authorities adopted based on the results of tax audits, which leads to the excessive restrictions’ problem on private property of organizations and individual entrepreneurs.   The study purpose is to substantiate the need to exclude interim measures of the tax authority from the Tax Code of the Russian Federation.   The study used an analysis of the regulatory legal framework, taxation practices, statistical data, and economic publications on interim measures of the tax authority. The conclusion is made about the presence in the existing mechanism of collecting taxes, penalties, fines of tax authorities’ numerous powers and other state bodies, duplicating each other, having an excessive nature and allowing, when used, to guarantee the decisions’ execution of tax authorities adopted based on the tax audits’ results without interim measures.